TOURIST EXPERIENCE AND ENVIRONMENTALLY RESPONSIBLE BEHAVIOUR – LITERATURE REVIEW - Tihana Cegur Radović (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The aim of the paper is a literature review of scientific papers on the concept of tourist experience and environmentally responsible behaviour. Furthermore, the aim is to determine future studies. The main research questions are: 1) Which research topics related to the tourist experience and environmentally responsible behaviour are in the literature? 2) Is there a connection between the tourist experience and environmentally responsible behaviour? 3) What are the directions for future research in the field? Literature was collected using the desk research method. An analysis of the content of the concepts tourist experience and environmentally responsible behaviour was made. The paper presents a review of the literature related to the tourist experience and environmentally responsible behaviour and their correlation and correlation with other constructs. The paper also provides a good theoretical basis for future empirical research. The paper uses a qualitative method of analysing scientific papers published in the period from 1987 to 2022. A total of 54 papers were analysed. The criteria for analysis were that they were academic articles, from the field of marketing, tourism and environmental protection, that they were peer-reviewed and in open access and they researched the concepts of tourist experience and environmentally responsible behaviour. Research in the field of tourism, marketing and environmental protection were analysed. Based on the analysis of the literature review, recommendations for future research are given. Further studies could be researched in some other fields other than tourism and marketing.